2017
DOI: 10.1371/journal.pone.0184761
|View full text |Cite
|
Sign up to set email alerts
|

Temporal patterns in road crossing behaviour in roe deer (Capreolus capreolus) at sites with wildlife warning reflectors

Abstract: Every year, there are millions of documented vehicle collisions involving cervids across Europe and North America. While temporal patterns in collision occurrence are relatively well described, few studies have targeted deer behaviour as a critical component of collision prevention. In this study, we investigated weekly and daily patterns in road crossing behaviour in roe deer. Using road crossing events and movement data obtained from GPS telemetry, we employed mixed-effect models to explain frequency and tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 48 publications
3
29
0
3
Order By: Relevance
“…A slightly different model (Sivic and Sielecki, 2001), the Strieter Lite WWR, was tested in 16 studies (e.g., Barlow, 1997;Riginos et al, 2015Riginos et al, , 2018. Other reflectors evaluated were WEGU (N = 2, e.g., Olbrich, 1984), AWIWA (N = 2, e.g., Voß, 2007), Bosch (N = 2, e.g., Gladfelter, 1984), Ruppert (N = 1, Queal, 1968), ITEK (N = 1, van den Berk, 2017), and Beutha reflectors (N = 3, Pluntke, 2014;Brieger et al, 2017a;Kämmerle et al, 2017) (cf. Supplementary Table 1).…”
Section: Methodological Differences and Results Of Wwr Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…A slightly different model (Sivic and Sielecki, 2001), the Strieter Lite WWR, was tested in 16 studies (e.g., Barlow, 1997;Riginos et al, 2015Riginos et al, , 2018. Other reflectors evaluated were WEGU (N = 2, e.g., Olbrich, 1984), AWIWA (N = 2, e.g., Voß, 2007), Bosch (N = 2, e.g., Gladfelter, 1984), Ruppert (N = 1, Queal, 1968), ITEK (N = 1, van den Berk, 2017), and Beutha reflectors (N = 3, Pluntke, 2014;Brieger et al, 2017a;Kämmerle et al, 2017) (cf. Supplementary Table 1).…”
Section: Methodological Differences and Results Of Wwr Studiesmentioning
confidence: 99%
“…From this perspective, the value of long-wavelength WWR is questionable and the likelihood of a reduction of WVC can be argued given the lack of animals' ability to perceive colors in these wavelengths (VerCauteren and Pipas, 2003). Modern WWR, produced and marketed in the past decade, are primarily blue (e.g., Brieger et al, 2017a;Beilharz, 2017 5 ;Kämmerle et al, 2017;Schilderwerk Beutha, 2017). However, independent studies evaluating the effectiveness of modern WWR in the field as well as the influence of blue light on feeding behavior in roe deer have not found any effect of the reflectors, either in reducing WVC directly or resulting in aversion or increased vigilance in roe deer (Brieger et al, 2017a,b;Kämmerle et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results confirm the observations made by Mysłajek et al (2016), where analogous relationship was reported. Furthermore, it is associated with a reduced tendency of wildlife migration and road crossing in winter (Kämmerle et al 2017). In winter, no individuals of some species were observed in the underpasses because, in Central Europe, many animals hibernate in winter (anurans, lacertids, hedgehogs, etc.)…”
Section: Discussionmentioning
confidence: 99%